Developing library spatial settings matrix through student learning behaviour / Norhayati Kassim and Azizah Md Ajis - Kassim, Norhayati; Md Ajis, Azizah (2018)
Many studies have investigated student learning behaviour (LB) in the academic library and reported that spatial setting provided sometimes could not facilitate the informal learning that took place. Does LB influence by the spatial setting or it is the other way round? This paper aims to understand these two factors that may give impact towards the design of academic library - the LB and the spatial setting. The first main objective is to identify the category of student LB by screening the activities occurred. The second is to examine how library spatial setting could facilitate the learning by investigating the activities conducted and how the space being utilized. In order to acquire the findings, content analysis method were used where keywords were identified before and during data analysis. All literature reviews were gathered from various types of journal, especially publishing in Journal Academic of Librianship. The literature regarding the learning behaviour, learning spaces and student preference space was observed during data analysis. From the findings, two groups of learning were discovered - 1) the individual learning, and 2) the group learning. Based on these, the Matrix Model of LB and Spatial Setting was developed which influences the style of learning - i) Individual/Private, ii) Individual/Public, iii) Group/Private, and iv) Group/Public. Besides that the environment, furniture design, technology and tools also contribute to the spatial setting preference and LB. This study will benefit library scholars, designer and librarian to plan the academic library in term of arrangement of space, furniture selection as well as tools and technology to be used